Development of a novel remote‐controlled and self‐contained audiovisual‐aided interactive system for immobilizing claustrophobic patients. (8th May 2015) - Ju, Harang; Kim, Siyong; Read, Paul; Trifiletti, Daniel; Harrell, Andrew; Libby, Bruce; Kim, Taeho
Abstract : In radiotherapy, only a few immobilization systems, such as open‐face mask and head mold with a bite plate, are available for claustrophobic patients with a certain degree of discomfort. The purpose of this study was to develop a remote‐controlled and self‐contained audiovisual (AV)‐aided interactive system with the iPad mini with Retina display for intrafractional motion management in brain/H&N (head and neck) radiotherapy for claustrophobic patients. The self‐contained, AV‐aided interactive system utilized two tablet computers: one for AV‐aided interactive guidance for the subject and the other for remote control by an operator. The tablet for audiovisual guidance traced the motion of a colored marker using the built‐in front‐facing camera, and the remote control tablet at the control room used infrastructure Wi‐Fi networks for real‐time communication with the other tablet. In the evaluation, a programmed QUASAR motion phantom was used to test the temporal and positional accuracy and resolution. Position data were also obtained from ten healthy volunteers with and without guidance to evaluate the reduction of intrafractional head motion in simulations of a claustrophobic brain or H&N case. In the phantom study, the temporal and positional resolution was 24 Hz and 0.2 mm. In the volunteer study, the average superior–inferior and right–left displacement was reduced from 1.9 mm to 0.3 mm and from 2.2 mm to 0.2 mm with AV‐aided interactive guidance, respectively. The superior–inferior and right–left positional drift was reduced from 0.5 mm/min to 0.1 mm/min and from 0.4 mm/min to 0.04 mm/min with audiovisual‐aided interactive guidance. This study demonstrated a reduction in intrafractional head motion using a remote‐controlled and self‐contained AV‐aided interactive system of iPad minis with Retina display, easily obtainable and cost‐effective tablet computers. This approach can potentially streamline clinical flow for claustrophobic patients without a head mask and also allows patients to practice self‐motion management before radiation treatment delivery. PACS number: 87.55.Gh